Is perception of excessive weight gain in a woman’s last pregnancy associated with less weight gain in her current pregnancy? - Hebert, Kasey M. (J Obstet Gynaecol, 2018)
We explored whether a woman’s perceptions of the appropriateness of her gestational weight gain (GWG) in her most recent prior pregnancy was associated with the altered weight gain in her current pregnancy. Parous pregnant women reported GWG in their most recent previous pregnancy and their perceptions of the appropriateness of this gain. GWG from the current pregnancy was abstracted from the obstetric records. On average, women (N = 57) were 29.8 (SD: 4.4) years old and 24.5 (SD: 6.5) weeks of gestation; 28% were overweight and 16% were obese before the current pregnancy. The median differences in the GWG across the pregnancies was −5 pounds (inter-quartile range [IQR]: −24,+2) for the women who thought their previous GWG was too much, +1 pounds (IQR: −10,+8) for the women who thought they gained the right amount, and +10 pounds (IQR: +5,+18) for the women who thought they gained too little. Further research is needed to understand how perceptions about previous GWG influences weight gain during subsequent pregnancies.